2013
DOI: 10.1371/journal.pone.0082940
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Metabolic Correlates of Perinatal White Matter Injury Severity

Abstract: Background and PurposeAlthough the spectrum of perinatal white matter injury (WMI) in preterm infants is shifting from cystic encephalomalacia to milder forms of WMI, the factors that contribute to this changing spectrum are unclear. We hypothesized that the variability in WMI quantified by immunohistochemical markers of inflammation could be correlated with the severity of impaired blood oxygen, glucose and lactate.MethodsWe employed a preterm fetal sheep model of in utero moderate hypoxemia and global severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Ischemia thus appeared to be necessary but not sufficient to generate necrotic or diffuse WMI. In preterm fetal sheep, the severity of WMI was significantly associated with the magnitude of hypotension, hypoxemia and hypoglycemia [152]. Collectively, these findings suggest that the propensity for more severe WMI is related to a combination of vascular anatomic immaturity, disturbances in cerebrovascular autoregulation and a variety of metabolic factors that may predispose to more severe energy failure in regions of focal white matter necrosis.…”
Section: Spectrum Of Focal and Diffuse Human White Matter Injurymentioning
confidence: 99%
“…Ischemia thus appeared to be necessary but not sufficient to generate necrotic or diffuse WMI. In preterm fetal sheep, the severity of WMI was significantly associated with the magnitude of hypotension, hypoxemia and hypoglycemia [152]. Collectively, these findings suggest that the propensity for more severe WMI is related to a combination of vascular anatomic immaturity, disturbances in cerebrovascular autoregulation and a variety of metabolic factors that may predispose to more severe energy failure in regions of focal white matter necrosis.…”
Section: Spectrum Of Focal and Diffuse Human White Matter Injurymentioning
confidence: 99%
“…Determining the target blood pressure range in very preterm infants (<28 weeks gestation) has been the subject of debate for several decades. Hypotension has been previously linked to the development of intraventricular hemorrhage ( 1 , 2 ) and white matter injury ( 3 ). Description of a normative set of blood pressure values in very preterm infants is confounded by varied methodology, heterogeneous patient populations used in prior studies, substantial changes in strategies for hemodynamic support and monitoring methodology, and survival rates among preterm infants since Versmold et al published the first normative data set in 1981.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, although conventional neuropathological review of paraffin-embedded tissue sections is widely employed by neuropathologists for diagnostic purposes, this approach lacked the sensitivity to distinguish control from VBI cases. In experimental models of preterm WMI, we found that pathology scores have markedly reduced sensitivity when WMI is in the mild to moderate severity range and more closely resemble controls (24). The fact that we detected group differences using optical fractionator, spaceballs, and process thickness measurements (but not with other methodologies) supports the utility of high-magnification and 3-dimensional stereological approaches to quantify the burden of astrogliosis across an unidentified cohort of cases with variable agerelated vascular injury and low AD burden.…”
Section: Discussionmentioning
confidence: 78%
“…We employed an ordinal rating scale to estimate the burden of reactive astrogliosis in the white matter using a protocol modified from Riddle et al, wherein astrogliosis was scored by a blinded neuropathologist (CDK) as follows: 0 (none); 1 (focal, < 25% of tissue involved); 2 (patchy, 25%-75% of tissue involved); and 3 (diffuse !75% of tissue involved) ( Fig. 2D) (24).…”
Section: Histopathological Analysis Of Injury By Ordinal Ratingmentioning
confidence: 98%
See 1 more Smart Citation